Influence of Yoga on Cancer-Related Fatigue and on Mediational Relationships Between Changes in Sleep and Cancer-Related Fatigue: A Nationwide, Multicenter Randomized Controlled Trial of Yoga in Cancer Survivors. (June 2019) - Lin, Po-Ju; Kleckner, Ian R.; Loh, Kah Poh; Inglis, Julia E.; Peppone, Luke J.; Janelsins, Michelle C.; Kamen, Charles S.; Heckler, Charles E.; Culakova, Eva; Pigeon, Wilfred R.; Reddy, Pavan S.; Messino, Michael J.; et al.
Background: Cancer-related fatigue (CRF) often co-occurs with sleep disturbance and is one of the most pervasive toxicities resulting from cancer and its treatment. We and other investigators have previously reported that yoga therapy can improve sleep quality in cancer patients and survivors. No nationwide multicenter phase III randomized controlled trial (RCT) has investigated whether yoga therapy improves CRF or whether improvements in sleep mediate the effect of yoga on CRF. We examined the effect of a standardized, 4-week, yoga therapy program (Yoga for Cancer Survivors [YOCAS©®]) on CRF and whether YOCAS©®-induced changes in sleep mediated changes in CRF among survivors.Study Design and Methods: Four hundred and ten cancer survivors were recruited to a nationwide multicenter phase III RCT comparing the effect of YOCAS©® to standard survivorship care on CRF and examining the mediating effects of changes in sleep, stemming from yoga, on changes in CRF. CRF was assessed by the Multidimensional Fatigue Symptom Inventory. Sleep was assessed via the Pittsburgh Sleep Quality Index. Between- and within-group intervention effects on CRF were assessed by analysis of covariance and 2-tailed t test, respectively. Path analysis was used to evaluate mediation.Results: YOCAS©® participants demonstrated significantly greater improvements in CRF compared with participants in standard survivorship care at post-intervention ( P < .01). Improvements in overall sleep quality and reductions in daytime dysfunction (eg, excessive napping) resulting from yoga significantly mediated the effect of yoga on CRF (22% and 37%, respectively, both P < .01).Conclusions: YOCAS©® is effective for treating CRF among cancer survivors; 22% to 37% of the improvements in CRF from yoga therapy result from improvements in sleep quality and daytime dysfunction. Oncologists should consider prescribing yoga to cancer survivors for treating CRF and sleep disturbance.